Associations between mindfulness and non-restorative sleep: the roles of resilience and handgrip - Li, Shuhan; Jiang, Yingting; Shen, Zhenrong; Liao, Yuan; Zeng, Yihao; Ye, Zengjie (Frontiers in Psychology, 2025)
AimThis study examined the mediating role of resilience and the moderating role of grip strength (handgrip) in the relationship between mindfulness and non-restorative sleep (NRS) and evaluated the non-linear association between mindfulness and NRS among university freshmen students.DesignThis is a cross-sectional descriptive study.MethodA total of 384 university students were recruited from Be Resilient to Nursing Career (BRNC) from two universities in June 2022. The Mindful Attention Awareness Scale, 10-item Connor–Davidson Resilience Scale, Non-restorative Sleep Scale, and handgrip were administered. Latent profile analysis, moderated mediation analysis, and generalized additive model analysis were performed.ResultsThe following three subgroups were identified through the latent profile analysis: low mindfulness (21%), medium mindfulness (49.4%), and high mindfulness (29.6%). While the significant mediating role of resilience between mindfulness and NRS was confirmed (SE = 0.041, p < 0.05), the moderating role of handgrip was not statistically significant. A non-linear relationship was verified between mindfulness and NRS.